Oscillation Criteria for Certain Even Order Neutral Delay Differential Equations - Ruba Al-Hamouri; Ali Zein (International Journal of Differential Equations)
We establish sufficient conditions for the oscillation of solutions of even order neutral type differential equations of the form [r(t)[x(t)+p(t)x(τ(t))](n−1)]′+q(t)f(x(σ(t)))=0.